The landscapes we eat: reconnecting people to food production through agri-toursim - Friederich, Yann (School of Architecture, Planning and Geomatics, 2023)
The production of the food we eat has an effect on the landscapes around us, from deforestation, to air and water pollution. The world grows 95% of its food in the uppermost layer of soil, making topsoil one of the most important components of our food system. Current conventional agricultural practices unfortunately degrade our soils. If we continue to degrade the soil at the rate we are now, the world could run out of topsoil in 60 years. If we want to repair our soils, we have to change the way we farm, to change the way we farm we have to change the way we consume. To change the way we consume we have to learn how our food is produced and the impacts thereof. My thesis intents to create a demonstration site where people can learn about various soil creation processes, whilst experiencing a landscape with rare and beautiful heritage. With the improvement of the socioeconomic and ecological conditions of the local community at the forefront.